Casados «en el Señor»: Relaciones de género en parejas testigos de Jehová - Kelly Marcela Velasco (La Manzana de la Discordia, 2018)
According the approaches of Weber and Durkheim, for whom religion is a social fact that drives people to lead a lifestyle according to different religious precepts to achieve salvation and based on the contributions to gender studies made by Butler, Scott, Rubin and Nicholson, this article aims to describe how gender relations are structured in the marriage of newlywed couples belonging to a congregation of Jehovah’s Witnesses in Cali. The documentary analysis of the sacred texts and interviews showed that the interpretation of religious precepts is associated with the primary and secondary sociability of individuals.